Untold war : new perspectives in First World War studies - Jones, Heather, 1978-; O'Brien, Jennifer; Schmidt-Supprian, Christoph (History of warfare ;, 2008)
Complex, brutal and challenging, the First World War continues to inspire dynamic research and debate. The third volume to emerge from the pioneering work of the International Society for First World War Studies, this collection of new essays reveals just how plural the conflict actually was - its totalizing tendencies are shown here to have paradoxically produced diversity, innovation and difference, as much as they also gave rise to certain similarities across wartime societies. Exploring the nature of this 'plural war, ' the contributions to this volume cover diverse themes such as combat, o.